Possible pitfalls in pressure transient analysis: Effect of adjacent wells - Ali Mirzaalian Dastjerdi; Asgar Eyvazi Farab; Mohammad Sharifi (Journal of Petroleum Exploration and Production Technology, 2019)
Abstract Well testing is one of the important methods to provide information about the reservoir heterogeneity and boundary limits by analyzing reservoir dynamic responses. Despite the significance of well testing data, misinterpreted data can lead us to a wrong reservoir performance prediction. In this study, we focus on cases ignoring the adjacent well’s production history, which may lead to misinterpretation. The analysis was conducted on both homogeneous and naturally fractured reservoirs in infinite-acting and finite-acting conditions. The model includes two wells: one is “tested well” and the other is “adjacent one.” By studying different scenarios and focusing on derivative plots, it was perceived that both reservoir and boundary models might be misinterpreted. Additionally, in all cases, a sensitivity analysis was performed on parameters affecting interpretation process. Studying the literatures, few articles have focused on drawbacks during diagnostic plot interpretation and also the effect of adjacent wells. Hence, these issues were addressed. Overall, considering several cases it was proved that neglecting the production effect of adjacent wells causes wrong interpretation, and this should be avoided in all interpretation cases. Regarding the importance of reservoir characteristics and its flow regime, any wrong interpretation may create huge uncertainties in the reservoir development. As a result, this paper aimed to address the well testing, especially in brown fields where the production of other wells may affect the pressure response of the tested well; therefore, it will be pivotal to consider the effect of adjacent wells’ production history. Graphic abstract